Using persuasive communication to co-create behavioural change – engaging with guests to save resources at tourist accommodation facilities. Issue 7 (3rd July 2017) - Warren, C.; Becken, S.; Coghlan, A.
ABSTRACT: Unsustainable consumption of energy and water by tourist accommodation will escalate if incremental global tourism growth and business-as-usual approaches continue. Guests use more than half of the energy and water at accommodation facilities and so have a partnership role to play in saving resources. Our study is the first to measure the impact of persuasive communication on guests' resource consumption behaviour (energy and water use) and stay satisfaction. It used an innovative intervention based on interpersonal communication, sequential influence and eco-feedback. Guests' ( n = 759) consumption of electricity, gas and water was monitored at four fully self-contained cottages using smart meters, over a period of 304 days. An ethnographic study, action research and departure survey examined if pro-environmental persuasion could encourage guests to save resources, how guests responded to the intervention and measured whether pro-environmental persuasion affected guest satisfaction. Results show that guests who received the intervention used significantly fewer resources, 80% claimed they tried to save and their overall satisfaction was not negatively affected, while reasons to save/not save were complex. A resource-saving persuasion model is proposed for further research, practitioners are recommended to install pro-environmental infrastructure, train staff to engage customers, and identify responsible channels for fiscal savings.